Elaboración de un mural en medio relieve basado en la iconografía de la cultura Puruhá, en el bloque B de la Facultad de Ciencias de la Educación, Humanas y Tecnologías de la Universidad Nacional de Chimborazo, año 2023 - Cabadiana Naranjo, Alvaro Bolívar (2023)
The research entitled: Elaboration of a mural in medium relief based on the iconography of the Puruhá Culture, in block B of the Faculty of Educational Sciences, Humanities and Technologies of the National University of Chimborazo, year 2023. The main objective of the research report was to analyze the iconography of the Puruhá culture and to indicate the use of the sculptural technique of medium relief and its different forms of application for the elaboration of a mural focused on the cultural, social and ancestral identity of the iconography of the Puruhá culture. . The methodology applied had a mixed approach, i.e., quali-quantitative, since the data collection technique used was an interview with one teacher as key informants of the Arts and Humanities Pedagogy Career to obtain information relevant to the research topic, in addition a survey of ten questions on a Likert scale was applied to 50 informants including authorities, teachers and students of the FCEHT. The results obtained were put under descriptive analysis to know the degree of need and acceptance to the realization of a mural in medium relief based on the iconography of the Puruhá culture. In this way, the paper details the whole process of elaboration of a mural on the exterior of block B of the FCEHT, detailing the process, from the sketching to the polychrome and lacquer sealing. All this is reflected in a photographic compendium.